Effect of Sr-Ti Molar Ratio on Strontium Titanate Prepared by Sol-Gel Method - Zhang, Wenjie; Bi, Feifei; Sun, Xin; He, Hongbo (Asian Journal of Chemistry, 2013)
Tetrabutyl titanate and strontium nitrate were used as initial materials in a sol-gel process to prepare strontium titanate. The effects of strontium-titanium molar ratio on phase composition, structure and photocatalytic activity of the prepared materials were studied. The produced material was mainly composed of SrTiO3 and TiO2 when n(Sr)/n(Ti) ratio was less than 1:1, while the materials containing mainly Sr2TiO4 were prepared at n(Sr)/n(Ti) higher than 1:1. The particles of all the samples presented irregular shape with rough surface, along with partly particles aggregation. Phase composition of the produced materials showed strong dependence on n(Sr)/n(Ti) ratio. The sample prepared with n(Sr)/n(Ti) of 1:1 possessed the optimal photocatalytic activity of 32.5 % after 0.5 h of irradiation.